IT for business (IT4B) : from genesis to revolution : a business and IT approach to digital transformation - Johnson, Brian; Zondervan, Walter (IT Governance Publishing Ltd, 2018)
This book reads like a conversation on IT service management. Rather than reinventing traditional IT frameworks or methods, IT4B provides a coherent understanding of digital readiness for your enterprise. It offers insight and coaching, rather than ready-made advice because not all businesses work best with a one-size-fits-all approach.